2019
DOI: 10.1177/0040517519896761
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of quality characteristics of cotton/elastane core yarn using artificial neural networks and support vector machines

Abstract: Core yarn is a type of yarn that has a filament fiber in the center with a different fiber wrapped around it. This type of yarn is of growing importance in the textile industry. It is important to predict the quality characteristics of a core yarn before production to prevent the faulty production of fabrics. Therefore, the development of predictive models is a necessity in the textile industry. In this study, artificial neural network (ANN) and support vector machine (SVM) models are proposed to predict the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The obtained results mainly depend on weights . The following equation represents the relationship between input and output of the network 35 , 36 : where, y is the output. is the j th input.…”
Section: Methodsmentioning
confidence: 99%
“…The obtained results mainly depend on weights . The following equation represents the relationship between input and output of the network 35 , 36 : where, y is the output. is the j th input.…”
Section: Methodsmentioning
confidence: 99%
“…The obtained results mainly depend on weights . The following equation represents the relationship between input and output of the network 42 , 43 : where, y is the output. is the j th input.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that ANN models provided significantly accurate prediction for yarn strength. Recently, Doran et al reported the utilization of ANN and support vector machine (SVM) methods to avoid faulty fabric production [ 28 ]. In addition, they used statistical tools i.e., analysis of variance (ANOVA) and principal component analysis (PCA) to overcome input dimensions.…”
Section: Classification Based On Textile Processesmentioning
confidence: 99%